Quantitative characteristic of Indonesian native chickens at the age of 4 months - Dika Irmaya; Depison Depison; Gushairiyanto Gushairiyanto (Livestock and Animal Research, 2021)
Objective: Native chickens (Kampung, Sentul, and Merawang) have great potential to be developed as both meat and egg producers. Quantitative data about native chickens are not widely known. The purpose of this research was to determine the quantitative characteristics of Native Chickens aged 1 month, 2 months, 3 months and 4 months.Methods: The research material is native chickens. The method used was an 82 sample in each strain and a total of 246 samples. The data collected is of a quantitative traits. Quantitative traits are traits that are influenced by multiple gene pairs, can be measured, and are heavily influenced by environmental factors. Data collected were analyzed using the average difference test (t-test). The average value vector of body measurements of chicken lines was analyzed using the T2-Hotelling statistical test. Main Component Analysis statistical test to identify the shape and size characteristics of each chicken strain. Data processing was assisted by using Minitab statistical software version 18.Results: The results of this study showed that body weight, weight gain and body size measurements of Kampung chicken were significantly different (P <0.05) higher than Sentul chicken and Merawang chickens. The identifier of the size of the Kampung chicken is the width of the chest, while the identifier of the shape is the length of the back. The identifier of Sentul chicken size is chest length, while the tibia is long. The characteristic of Merawang chicken is the length of the tibia, while the character of the shape is the wing length.Conclusions: Quantitative characteristics (body weight, weight gain and body size measurements) at the age of 4 months Kampung chickens more heavily than Sentul chicken and Merawang chicken.